WOMEN IN THE POLITICAL DEVELOPMENT OF NIGERIA: THE GOODLUCK JONATHAN PRESIDENCY - Jaja, Jones (Acta Scientiae et Intellectus, 2024)
The contributions of women in the socio-political and economic development of women had often been sidelined or totally neglected in the history of Nigeria. It is time for continual advocacy of the role of woman in the transformation of the nation. Hitherto, the contributions of women in the economic, child rearing and management of the home has been documented in some areas of out nation. Only a few communities had projected the political contribution of women their societies in the pre-colonial and colonial period. The port independent period saw little documentation of the political contribution of women in Nigeria. However, the period 2011 – 2015 witness more women playing key roles in the political equation of the nation. The relevance of the womenfolk has never been more felt during the Jonathan administration. This no doubt could be attributed to the education and empowerment of women. This paper examines the contribution of women through the period to the Jonathan Presidency.